MEMS Pressure Sensors with Novel TSV Design for Extreme Temperature Environments - Muhannad Ghanam; Peter Woias; Frank Goldschmidtböing (Sensors)
This study introduces a manufacturing process based on industrial MEMS technology, enabling the production of diverse sensor designs customized for a wide range of absolute pressure measurements. Using monocrystalline silicon as the structural material minimizes thermal stresses and eliminates temperature-dependent semiconductor effects, as silicon functions solely as a mechanical material. Integrating a eutectic bonding process in the sensor fabrication allows for a reliable operation at temperatures up to 350 °C. The capacitive sensor electrodes are enclosed within a silicon-based Faraday cage, ensuring effective shielding against external electrostatic interference. An innovative Through-Silicon Via (TSV) design, sealed using gold–gold (Au-Au) diffusion and gold–silicon (Au-Si) eutectic bonding, further enhances the mechanical and thermal stability of the sensors, even under high-temperature conditions. The unfilled TSV structure mitigates mechanical stress from thermal expansion. The sensors exhibited excellent performance, achieving a linearity of 99.994%, a thermal drift of −0.0164% FS (full scale)/K at full load and 350 °C, and a high sensitivity of 34 fF/kPa. These results highlight the potential of these sensors for high-performance applications across various demanding environments.